(untitled) - Gribbins, Joseph (New York, 2001)
From the traditional small boat to the elegant speedboat to the magnificent yacht, celebrate these breathtaking vessels in beautiful wood. A portrait of speed, lavishness, and grace in the water.
Keywords: Thuyền gỗ,Wooden boats